Arthur's great big valentine - Hoban, Lillian (New York, N.Y. : Harper & Row, 1989)
After they have a falling out, Arthur and his best friend Norman make up with very special valentines.
Keywords: Friendship -- Fiction; Valentine's Day -- Fiction; Chimpanzees -- Fiction